PENERAPAN BIAYA STANDAR DENGAN PENDEKATAN BIAYA PENUH DALAM MENGHITUNG HARGA POKOK PRODUKSI PROTOTIPE TEKO HIJAU BERDEKORASI PATRA PUNGGEL (D 17,5 CM – T 14,5 CM) SEBAGAI DASAR PENENTUAN HARGA JUAL DAN PERSEDIAAN AKHIR, SERTA PENGARUHNYA TERHADAP LAP - I Nyoman Normal; I Wayan Wardita (Forum Manajemen, 2013)
The aims of this research that relate for the green teapot prothotype whichdecorate of patra punggel (d 17,5 cm – h 14,5 cm) were : (1) To calculatecost ofgood manufactured; (2) To determine cost price; (3) To recognized ending inventory;and (4) To knew the influences of financial variable to financial statements currentperiod. The research results shew that : (1) Cost of good manufactured the greenteapot prothotype which decorate of patra punggel (d 17,5 cm – h 14,5 cm) actuallywas Rp 73.625,00 each unit, that followed by raw materal cost Rp 38.750,00, directlabour cost Rp 15.500,00, variable ovrehead cost Rp 11.625,00, and fixed overheadcost Rp 7.750,00, but according to Standard Costing systems (theoretically) was Rp85.698,44 each unit, that followed raw materal cost Rp 38.750,00, direct labourcost Rp 40.589,10, variable ovrehead cost Rp 4.688,71, and fixed overhead costRp 1.670,63. Cost of good manufactured green teapotprothotype actually smallerthan theoretically Rp 12.073,44; (2) Cost price the green teapot prothotype actuallywas Rp 84.668,75 each unit, that priceformed by cost ofgood manufactured Rp73.625,00 expected profit margin Rp 3.681,25, and operation expense Rp 7.362,50(marketing expense Rp 4.417,50 and general & administration expense Rp 2.945,00),but according to full cost pricing method (theoretically), cost price was Rp 98.553,20each unit, that priceformed by cost of good manufactured Rp 85.690,44, expectedprofit margin Rp 4.284,92, and operating expense Rp 8.569,04(marketing expenseRp 5.141,90 and general & administration expense Rp3.427,93). Cost price greenteapotprothotype actually smaller than theoretically Rp 13.884,45;(3) Endinginventory of green teapotprothotype actually was Rp 4.417.500,00, but accordingto Special identification (theoretically), ending inventory was Rp 5.141.906,40.Ending inventory of green teapot prothotype actually smaller than theoretically Rp 724.416,40; and (4) Financial variable actually that followed by cost of goods manufactured, cost price, and ending inventory green teapotprothotype causedfinancial statements actuallywas understated.